From “punks” at school to “superstars” at work: Social capital and educators’ asset-based perspectives of students in high school internships - Kundu, Anindya; McLeod, Scott; Piedrahita-Guzmán, Yuly (Frontiers in Education, 2024)
High school internships provide students with valuable work-based learning experiences, career-oriented networking, and in-demand professional skills. In this study of high school principals, internship coordinators (“institutional agents”), and student interns, we highlight data from interviews and focus groups that substantiate the idea that internships can showcase students’ more diverse and latent aptitudes but are more effective when building upon students’ existing interests and abilities. Given the opportunity-focused goals of these programs, we recommend that school-based professionals adopt the language of social capital (or similar frameworks) to develop shared understandings between stakeholders and also critique existing conceptualizations to approach the work from asset-based and equity lenses.